Transcranial Direct Current Stimulation: Considerations for Research in Adolescent Depression - Lee, Jonathan C.; Lewis, Charles P.; Daskalakis, Zafiris J.; Croarkin, Paul E. (Frontiers in Psychiatry, 2017)
Adolescent depression is a prevalent disorder with substantial morbidity and mortality. Current treatment interventions do not target relevant pathophysiology and are frequently ineffective, thereby leading to a substantial burden for individuals, families, and society. During adolescence, the prefrontal cortex undergoes extensive structural and functional changes. Recent work suggests that frontolimbic development in depressed adolescents is delayed or aberrant. The judicious application of non-invasive brain stimulation techniques to the prefrontal cortex may present a promising opportunity for durable interventions in adolescent depression. Transcranial direct current stimulation (tDCS) applies a low-intensity, continuous current that alters cortical excitability. While this modality does not elicit action potentials, it is thought to manipulate neuronal activity and neuroplasticity. Specifically, tDCS may modulate N-methyl-d-aspartate receptors and L-type voltage-gated calcium channels and effect changes through long-term potentiation or long-term depression-like mechanisms. This mini-review considers the neurobiological rationale for developing tDCS protocols in adolescent depression, reviews existing work in adult mood disorders, surveys the existing tDCS literature in adolescent populations, reviews safety studies, and discusses distinct ethical considerations in work with adolescents.